Otok sredi Evrope? - Kukavica, Jaka (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
This paper examines the role of the Supreme Court of the Republic of Slovenia in judicial dialogue in Europe by analysing cross-citations between the supreme courts of EU Member States. It differentiates between active participation of the Supreme Court in judicial dialogue—cross-citations made by the Supreme Court to other European supreme courts—and passive participation—cross-citations made by other European supreme courts to the decisions of the Slovenian Supreme Court. We identified such cross-citations by searching for pre-determined key words in databases of decisions of supreme courts in all 28 EU Member States. In the statistical population of about 1,330,000 decisions delivered by supreme courts in the EU in 2000–2018 in private law cases, we identified almost 3,000 cases in which European supreme courts made cross-citations. Put in a comparative context, the Supreme Court engages in judicial dialogue with moderate frequency: it made cross-citations to European supreme courts in 63 cases with a heterogeneous citation pattern, which is analysed in detail by the paper. Conversely, the Supreme Court is only rarely passively engaged in judicial dialogue: only once has a foreign supreme court referenced its decision. However, such nearly complete isolation is characteristic of other supreme courts of newer and smaller EU Member States with a working language that is not widely spoken as well. The paper offers a reflection on what might be necessary for the Supreme Court to put itself more firmly onto the European map as an equal interlocutor to other more established supreme courts.
Keywords: Evropa; medsodniški dialog; primerjalno pravo; sodišča; vrhovna sodišča; Vrhovno sodišče Republike Slovenije